Simulating Bending Failure of Ice using Smoothed Particle Hydrodynamics: A re-usable framework for simulating of fluid problems using SPH - Koning, Jasper (author) (2019)
The offshore industry is a conservative industry, sticking to rigid best-practices and reluctant to try new techniques. A promising new technique that hasn't found much adoption in offshore industry is SPH. This thesis aims to improve the reach and use of SPH within the offshore industry. With an abundance of world's unexplored hydrocarbons located in the Arctic Region, 18%, ice-structure interactions (ISI) are set to increase. Modeling these ISI requires complex dynamics, SPH can model these ISI dynamics without extra treatment. SPH works by interpolation of a set of neighbouring particles using a weighing function. This modeling technique offers many advantages over conventional rules-of-thumb, Finite Element Modeling (FEM), and Finite Volume (FV) methods. SPH is a particle based method, thus, uniquely suited for problems with large displacements, or discontinuities. However, in the standard, weakly-compressible (WCSPH) method spurious pressure fluctuations and particle clustering can occur. By implementing the plethora of correction methods and equations present in literature, such as kernel corrections, incompressible variants, or density corrections, these drawbacks can be circumvented and a robust framework can be formed. An implementation of WCSPH that focuses on adaptability and flexibility is presented in this work. The flexibility of the implementation allows future researchers to focus on the core of their research, only changing the equations they are interested in, instead of implementing all the required equations for a full SPH simulation. A validation study of the implementation assures that it matches closely with existing implementations and real-world results. The mathematical model developed in Keijdener (2018) is implemented in the proposed WCSPH implementation. Comparing the results shows close agreement for the breaking length. However, significant differences are present in the failure time results. Despite this it shows the possibility of combining solid mechanics with SPH, and ...